2006
DOI: 10.1007/s10067-006-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

A study of male patients with forearm fracture in Northern Ireland

Abstract: Osteoporosis, although considered less common, still occurs in men. We present a cross-sectional study of a group of Northern Ireland men with low-trauma forearm fractures to determine the presence of osteoporosis and screen for secondary causes of low bone mineral density. Male patients aged 30-75 years, presenting with distal forearm fracture in 2000-2001 in Northern Ireland, were identified through a Colles fracture database. A total of 37 subjects consented to have bone mineral density measurements underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…In these periods, 50 and 24 % of our patients were deficient, respectively. Wright et al [ 31 ] found in 18/37 (49 %) male patients with a distal forearm fracture living in Northern Ireland a vitamin D deficiency. Of the 49 male patients with a distal forearm fracture in our study, 20 (41 %) were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these periods, 50 and 24 % of our patients were deficient, respectively. Wright et al [ 31 ] found in 18/37 (49 %) male patients with a distal forearm fracture living in Northern Ireland a vitamin D deficiency. Of the 49 male patients with a distal forearm fracture in our study, 20 (41 %) were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found a vitamin D deficiency (serum calcidiol <50 nmol/L) prevalence varying between 22 and 100 % [ 6 30 ]. Studies in non-hip or osteoporotic fracture patients found vitamin D prevalences of 13–50 % [ 31 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Submariners are also subjected to prolonged exposure to elevated CO 2 concentrations (ranging be-tween 0.7 and 1.0%) compared with atmospheric air (0.03% CO 2 ). It is common knowledge that breathing of CO 2 excess induces hypercapnia and further deregulation of acid/base homeostasis (3,8,28,35,42). According to the Henderson-Hasselbalch equation, a close relationship exists between blood pH, PCO 2 , and HCO 3…”
Section: Discussionmentioning
confidence: 99%
“…In adults, vitamin D deficiency leads to secondary hyperparathyroidism, increases bone turnover, leading to progressive bone loss, and further heightens the risk for osteoporosis (16). Moreover, a recent cross-sectional study performed on a group of Northern Irishmen exhibiting low-trauma forearm fractures showed that vitamin D deficiency may possibly account for mineral density lessening [bone mineral density (BMD) measurements], increasing thereby conditions for further broken bone (42).…”
mentioning
confidence: 99%
“…The role of vitamin D in bone mineralization, growth, and remodeling is well-known and documented [22][23][24]. In a study examining 37 male patients from 30 to 75 years old with distal forearm fractures, 49 % of these had vitamin D insufficiency, defined as serum levels between 20 and 30 ng/mL, or deficiency, defined as serum levels less than 20 ng/mL [25]. Jang et al looked at 104 postmenopausal women treated surgically for DRF, along with 107 age-matched controls.…”
Section: Epidemiology/risk Factorsmentioning
confidence: 99%